Material for relieving thermal injury and pain caused by laser and microneedle and medical instrument thereof
By combining CuMOF@AA material composed of copper ions and Centella asoxalic acid with lidocaine, microneedle patches were prepared, which solved the problems of thermal damage and pain in laser treatment, and achieved effective cell protection and pain relief effects.
Patent Information
- Application Number
- CN202411685353.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-22
AI Technical Summary
The application of laser treatment in dermatology and plastic surgery can cause thermal damage and pain. The existing local anesthetic drugs such as creams have a long time to take effect and limited subcutaneous penetration depth, which is not effective.
The metal organic frame material (CuMOF@AA) composed of copper ions and citoxalic acid is prepared to achieve transdermal administration by heating under alkaline conditions to form sheet-like particles, combined with lidocaine. Relieves heat damage and pain.
CuMOF@AA@Lidocaine microneedle significantly reduces the stress response of cells after heat damage, protects cells, reduces apoptosis, effectively relieves pain and inflammatory responses, and improves skin repair effects.
Smart Images

Figure CN119454755A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an organic microparticle material, in particular to a metal organic framework material, application of the material in alleviating thermal damage and pain caused by laser treatment, and a microneedle and a medical device thereof. Background Art
[0002] Ablative lasers, represented by carbon dioxide fractional lasers, are widely used in dermatology and plastic surgery. The main principle is focal photothermal effect, using array-like laser beams to act on the skin surface, especially the dermis, to stimulate the production of dermal collagen and the rearrangement of collagen fibers, and promote the repair of skin tissue and the decomposition of pigments, thereby achieving multiple effects such as improving skin quality, repairing scars, removing wrinkles, removing spots and beautifying the skin, and shrinking pores.
[0003] Skin burns are a common adverse reaction to ablative lasers. Taking carbon dioxide fractional lasers as an example, when acting on the skin, it will produce thermal damage such as thermal effects, thermal ablation and thermal coagulation, with the highest temperature reaching 100°C. Improper operation or inappropriate parameter settings will cause thermal damage to the skin of varying depths, causing skin inflammation, and in severe cases, may cause pigmentation and scarring.
[0004] In traditional Chinese medicine, Centella asiatica (L.) Urban, a plant of the Umbelliferae family, is believed to have anti-inflammatory and anti-scarring effects (Int J Mol Sci, 2024, 25(2)). Modern studies have found that Asiatic acid (AA), an organic component extracted from Centella asiatica, can effectively inhibit the activation and proliferation of inflammatory cells and inhibit the expression of inflammatory factors such as IL-6, TNF-α and PGE2 by macrophages, thereby effectively reducing tissue damage and inflammatory response (FASEB J, 2024, 38(9): e23645, Int Immunopharmacol, 2017, 50: 313-318). However, due to the extremely low solubility of AA in water, its availability in vivo is directly limited (Photochem Photobiol, 2020, 96(1): 124-138). Summary of the invention
[0005] One object of the present invention is to provide a composite material that is beneficial to improving the solubility of asiatic acid and thus improving the bioavailability.
[0006] Another object of the present invention is to provide a combined material that acts on the skin to alleviate thermal damage caused by laser treatment.
[0007] Another object of the present invention is to provide an application of a composite material in the preparation of a medical device for alleviating thermal damage caused by laser treatment.
[0008] Another object of the present invention is to provide a microneedle comprising lidocaine for alleviating thermal damage caused by laser treatment.
[0009] Copper ion (Cu 2+ ) as a coenzyme can participate in the cross-linking process of collagen and elastin in the extracellular matrix by regulating enzyme activity, affecting collagen maturation (Am J Clin Nutr, 1979, 32(4): 856-71). Studies have found that Cu 2+ It also has a certain anti-inflammatory effect and can reduce the damage to cells caused by oxidative stress (Int Immunopharmacol, 2017, 50: 313-318). In the present invention, it is combined with AA to produce a synergistic effect of alleviating heat damage.
[0010] A composite material comprises copper ions and asiatic acid in a weight ratio of 1:0.9-1.
[0011] Another composite material is a MOF structure composed of copper ions and Centella asiatica acid, and the weight ratio of copper ions to Centella asiatica acid is 1:0.9~1.
[0012] The composite material of the present invention is self-assembled by heating copper ions and asiatic acid under alkaline conditions (such as pH>11) (such as 70°C±2°C) for 24 hours.
[0013] The composite material of the present invention is a flaky particle with an average particle diameter of 236.8 nm.
[0014] In the composite material of the present invention, copper and oxygen are crystalline-bonded.
[0015] The composite material of the present invention further comprises lidocaine, so as to facilitate the application of the composite material in treating thermal damage caused by laser treatment, with a content of 8.6wt%±0.4wt%.
[0016] The composite material of the present invention is mixed with a biodegradable polymer forming a gel (such as but not limited to PLGA, PLA, PGA and PLL, etc.) as a base material to form a microneedle patch, which includes an array of microneedles arranged on the patch, and the microneedle height is 400μm±20μm.
[0017] The present invention prepares a novel MOF structural material (CuMOF@AA) by using Cu ions and AA. The material can fully utilize the biological properties of Cu ions and AA to reduce the inflammatory response in the wound microenvironment, while utilizing the degradation process of the MOF material in the body to achieve controlled release of AA, and can also avoid the safety risks that may be caused by direct oral administration or injection of copper as a heavy metal.
[0018] In addition, due to the photothermal effect, patients experience significant pain during the use of ablative lasers. In clinical practice, local anesthetics such as lidocaine cream are usually applied before the operation to relieve the pain. However, cream-based local anesthetics have the disadvantages of long onset time and limited subcutaneous penetration depth during use. Clinical observations show that the actual analgesic effect of laser treatment is not good.
[0019] The microneedles provided by the present invention, especially the microneedle patch made of a soluble substrate, realize transdermal drug delivery. The needle body contains functional drug ingredients and can penetrate the skin to different depths according to the length of the needle tip. The drug is released as the needle body dissolves, achieving efficient penetration and absorption of subcutaneous tissue and the human body without leaving obvious damage to the epidermis. The pain, bleeding and infection risks of traditional injection methods can be effectively avoided, and the use is simple and comfortable.
[0020] It has been verified that in vitro CuMOF@AA@Lidocaine microneedle solution can reduce the stress changes of cells after thermal damage, and there is no significant increase in HSP70 protein content and mRNA expression. It is also confirmed that the number of cell deaths caused by CuMOF@AA@Lidocaine microneedle has no significant change, which effectively protects cells and reduces cell apoptosis caused by thermal damage.
[0021] Experiments in experimental animals have shown that CuMOF@AA@Lidocaine microneedles not only significantly improved the animals' pain response, but also effectively relieved the inflammatory response caused by thermal damage and reduced the damage to tissues caused by high heat. They are suitable as medical devices to relieve pain during laser treatment and thermal damage to the skin. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a bright field photo of the prepared CuMOF@AA powder;
[0023] Figure 2 This is a bright field photo of the CuMOF@AA microneedle array;
[0024] Figure 3 This is the electron microscope image of CuMOF@AA powder under the FE-SEM field of view;
[0025] Figure 4 This is the DLS particle size result of CuMOF@AA powder;
[0026] Figure 5 The element analysis results of CuMOF@AA powder are shown as follows: C, O, and Cu;
[0027] Figure 6 XRD detection diagram of CuMOF@AA powder;
[0028] Figure 7This is the UV spectrophotometric detection diagram of CuMOF@AA solution;
[0029] Figure 8 This is the electron microscope image of the CuMOF@AA-Lidocaine microneedle patch under the FE-SEM field of view;
[0030] Fig. 9 The following are tissue sections after the CuMOF@AA-Lidocaine microneedle patch was inserted; A is a puncture effect diagram presented by a paraffin section of mouse skin, and B is a puncture effect diagram presented by a frozen section of a human scar skin;
[0031] Fig.10 The results of HSP70 in each group of cells after heat damage; A is the electrophoresis results of HSP70 protein and its statistical diagram, B is the statistical diagram of the changes in the expression of HSP70-related gene mRNA, * indicates that compared with the Ctrl-neg group, p < 0.05; # indicates that compared with the Ctrl-pos group, p < 0.05;
[0032] Fig.11 The dead cell staining results of each group after thermal injury; A is the staining image under the visual field, B is the statistical graph of the staining count results, * indicates: compared with the Ctrl-neg group, p < 0.05; # Means: compared with the Ctrl-pos group, p < 0.05;
[0033] Fig.12 The analgesic and anti-heat injury effects of the CuMOF@AA-Lidocaine microneedle patch were evaluated in a skin burn model; A is a bright field photograph of the skin of animals in each experimental group before (Pre), after (Post) and after modeling (Post-burn) with lidocaine cream (Ctrl group) or CuMOF@AA-Lidocaine microneedle (MN group); B is the frequency of rabbit withdrawal during the burn process, *p<0.05; C is the result of HE staining of each experimental group at 3 days (3day) and 7 days (7day), respectively. DETAILED DESCRIPTION
[0034] The technical solution of the present invention is described in detail below with reference to the accompanying drawings. The embodiments of the present invention are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention is described in detail with reference to the preferred embodiments, it should be understood by those skilled in the art that the technical solution of the invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
[0035] Example 1 Preparation and characterization of CuMOF@AA microneedles
[0036] Dissolve 120 mg CuCl2·2H2O and 50 mg asiatic acid in 20 mL of deionized water with a pH value of >11 (modulated with 10 mol / L NaOH), stir thoroughly and heat the mixture in a light-proof water bath at 70°C for 24 h. Collect the turbid liquid, centrifuge at 12000 rpm for 15 min at 4°C, discard the supernatant, and resuspend and wash twice with anhydrous ethanol and deionized water respectively. After washing, centrifuge at 20000 rpm for 10 min. Collect the dark gray solid at the bottom and freeze-dry to obtain a brown powder (such as Figure 1 ).
[0037] The brown powder obtained by synthesis was photographed using FE-SEM, and it can be seen that Cu and AA self-assembled under alkaline conditions to synthesize flaky particles of uniform size (such as Figure 3 ).
[0038] The average particle size of the brown powder detected by DLS is 236.8 nm ( Figure 4 ).
[0039] According to the elemental energy spectrum analysis, carbon (C), oxygen (O) and copper (Cu) are evenly distributed in the brown powder particles (e.g. Figure 5 ), and its content (w%) is approximately 28.16%, 29.10% and 42.74%.
[0040] XRD analysis showed that the crystal structure peaks of the brown powder particles were consistent with the characteristic peaks of CuO nanocompounds (such as Figure 6 ), which shows that this example successfully synthesized a material with a complete crystal structure.
[0041] In addition, UV spectrophotometry detected that the brown powder solution was stable and showed an absorption peak at 250nm ( Figure 7 ), which is also consistent with the absorption spectrum of Centella asiatica total glycosides at 276nm in the literature.
[0042] These results prove that this example obtains a MOF structured nanoparticle stabilized by Cu and asiatic acid, which is denoted as CuMOF@AA.
[0043] Example 2 Preparation and characterization of CuMOF@AA microneedle patch
[0044] Dissolve the CuMOF@AA powder in 20 mg / mL lidocaine hydrochloride and dilute to 4 mg / mL. Add 600 μL of the diluted CuMOF@AA-lidocaine solution to 350 mg of γ-PGA. Ultrasonicate at room temperature for 20 min to fully disperse. Centrifuge at 12000 rpm at 4 °C for 15 min to remove bubbles to obtain CuMOF@AA gel.
[0045] The CuMOF@AA gel was filled into the PDMS microneedle mold and centrifuged at 3000 rpm at room temperature to remove bubbles. The excess gel around was then wiped with a cotton swab, and the filled mold was placed in an oven at 40°C overnight. After the microneedles were dried, they were demolded and used to obtain a CuMOF@AA microneedle array sheet (such as Figure 2 ).
[0046] like Figure 8 FE-SEM images show that the CuMOF@AA-Lidocaine microneedle patch has a four-sided pyramidal microneedle arranged in a matrix, with a base length of about 260 μm and a height of about 400 μm. Fig. 9 A) and human scar skin ( Fig. 9 B) can penetrate the epidermis to depths of >300μm and >100μm respectively.
[0047] HPLC liquid chromatography detection showed that the lidocaine content in the CuMOF@AA-Lidocaine microneedle patch was approximately 8.6% (w / w).
[0048] Example 3 In vitro experiment on the resistance of CuMOF@AA-Lidocaine microneedles to thermal damage
[0049] Prepare a solution of ethylene oxide-sterilized CuMOF@AA-Lidocaine microneedle patches at a ratio of 2 patches / 40 mL DMEM cell culture medium, and prepare equal concentrations of γ-PGA / DMEM solution and lidocaine / DMEM solution. After treating skin fibroblasts with DMEM culture medium, CuMOF@AA-Lidocaine solution, γ-PGA / DMEM solution and lidocaine / DMEM solution for 15 minutes, the culture dishes were placed in a 45°C water bath for heat treatment for 10 minutes, and then the cells in each group were collected to detect the expression of heat shock protein 70 (HSP70). Under normal physiological conditions, HSP70 in cells is expressed at a basic level, but under in vitro environmental stress conditions such as high temperature, cold, and hypoxia, the synthesis rate of HSP70 increases significantly. Fig.10 As shown, compared with skin fibroblasts before heat treatment (Ctrl-neg), the HSP70 content of skin fibroblasts treated with no special treatment (Ctrl-pos), γ-PGA solution (γ-PGA) and lidocaine solution (Lidocaine) increased after heat injury, while the HSP70 protein content of cells treated with CuMOF@AA@Lidocaine solution (CuMOF@AA@Lido) after heat injury was increased. Fig.10 A) and mRNA expression ( Fig.10B) There was no significant increase, proving that the CuMOF@AA@Lidocaine microneedle solution in vitro can reduce the stress changes in cells after thermal injury.
[0050] In another set of cell experiments, we used propidium iodide (PI) to stain each group of cells after heat treatment. PI cannot pass through the membrane of living cells, but can pass through damaged cell membranes to stain the cell nucleus (red fluorescence), so it is used to detect cell apoptosis. Fig.11 As shown in the figure, compared with Ctrl-neg, the number of dead cells in the Ctrl-pos, γ-PGA and Lidocaine groups increased significantly after thermal injury, while the number of dead cells in the CuMOF@AA@Lido group did not change significantly. This further proves that CuMOF@AA-Lidocaine can effectively protect cells in vitro and reduce cell apoptosis caused by thermal injury.
[0051] Example 4 In vivo experiment on analgesic effect and anti-thermal injury effect of CuMOF@AA-Lidocaine microneedles
[0052] like Fig.12 As shown in A, the hair on the back of 3-6 month old male New Zealand white rabbits was fully removed with a razor and depilatory cream, and the control group (Ctrl group) was smeared with compound lidocaine cream (containing 25 mg lidocaine per gram), and the experimental group (MN group) used the thumb perpendicular to the skin to continuously press the CuMOF@AA-Lidocaine microneedle for 1 minute, so that the needle tip penetrated the subcutaneous tissue and fully dissolved, and repeated 3 times. After wiping the surface drug with a 75% alcohol cotton ball, it can be seen that the skin of the experimental group after microneedle puncture was gray-black, indicating that the needle tip components can effectively penetrate into the subcutaneous tissue.
[0053] Then, referring to the literature, the laser temperature range for skin treatment is 60-100°C (Adv Wound Care (New Rochelle), 2021, 11(4): 163-178), which can cause epidermal damage, skin inflammatory response, collagen production and other pathological changes similar to conventional burns (Cell Biochem Biophys, 2013, 67(3): 1005-1014). Therefore, a 100°C pointed electric soldering iron was used to simulate the laser to create 9 thermal damage points in a 3×3 matrix within the drug treatment range, and the above experiment was repeated 4 times.
[0054] The frequency of the rabbit's flinching during the hot spot process (= total number of flinching times / total number of times) was used to reflect the degree of skin pain under different treatment methods. Fig.12As shown in B, the average withdrawal frequency of the experimental group was 0.1, and that of the control group was 0.36, indicating that the analgesic effect of the CuMOF@AA-Lidocaine experimental group was better.
[0055] After 3 days, Fig.12 As shown in A, the lesion area of the experimental group (MN group) was light pink, with clear edges and a slightly rough surface but generally smooth. The lesion area of the control group (Ctrl group) was darker in color, showing brown, with a significantly rough surface, irregular edges, and obvious blood scab formation, indicating that the experimental group had a better repair effect after thermal injury. The skin at the modeling site was taken for HE staining, and the results were as follows Fig.12 C. At 3 days, compared with the control group, the depth of epidermal damage in the experimental group was smaller, and the degree of inflammatory cell infiltration (single-pointed arrow) was lighter. At 7 days, the experimental group still had no scab (black five-pointed star), and the epidermal thickening was more obvious than that in the experimental group (double-pointed arrow). It shows that although the epidermis of the experimental group using the CuMOF@AA-Lidocaine microneedle of this embodiment was thermally damaged, the damage to its epidermis was milder, the skin inflammatory reaction was smaller, and the epithelialization was more mature.
Claims
1. A composite material, characterized in that It comprises copper ions and asiatic acid in a weight ratio of 1:0.9-1.
2. The composite material according to claim 1, characterized in that MOF structure composed of copper ions and Centella asiatica acid.
3. The composite material according to claim 2, characterized in that It is self-assembled by heating copper ions and Centella asiatica acid under alkaline conditions.
4. The composite material according to claim 1, characterized in that It is a flake-like particle.
5. The composite material according to claim 4, characterized in that The average particle size is 236.8 nm.
6. The composite material according to claim 1, characterized in that Copper is crystalline bonded with oxygen.
7. The composite material according to claim 1, characterized in that Also includes lidocaine.
8. The composite material according to claim 1, characterized in that Also included are biodegradable polymers for making the microneedles.
9. Use of the composite material according to any one of claims 1 to 8 in the preparation of medical devices for alleviating laser-induced thermal damage and pain.
10. A microneedle, characterized in that The invention comprises the combined material according to any one of claims 1 to 8.
Citation Information
Patent Citations
Preparation method of metal-supported multilevel porous channel HKUST-1 benzene desulfurization catalyst
CN108514891A
Biological material, preparation method of biological material, and application of biological material in bone repair
CN110538345A
Microneedle patch and application thereof in wound healing
CN113577012A
Spray-dried metal-organic frameworks for treatment and / or diagnosis of pulmonary disease
US20230398112A1